DESIGNING PISA-LIKE MATHEMATICS TASK USING A COVID-19 CONTEXT (PISACOMAT) - Nusantara, Duano Sapta; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2021)
New changes to the school curriculum by enacting a minimum competency assessment (MCA) with PISA criteria in 2021 have led to confusion over the form of MCA questions among teachers and students due to limited learning resources at schools. This study aimed to produce valid and practical PISA COVID-19 mathematics tasks (PISAComat) potentially affecting mathematics literacy. This study involved 27 secondary-level students aged 15 years old with different levels of mathematics skills. Design research in the form of development studies was chosen as the core framework of this research assisted with the online learning platform. Data were analyzed descriptively through observations, tests, interviews, and document reviews. A set of PISAComat on quantity and change & relationship at the level of reasoning was gained after a formative evaluation. The formative process was conducted through zoom meetings and intensive communication at WhatsApp Group (WAG) to produce valid and practical PISAComat. After being tested in the classroom, the resulting PISAComat had been potentially effective in promoting students' mathematics literacy and life skills during the COVID-19 pandemic.